Ski boot soles based on a glass fiber/rubber composite with improved grip on icy surfaces - Colonna, M.; De Bon, F.; Tarterini, F.; Moncalero, M.; Totaro, G.; Gioia, C.; Fabbri, P. (Procedia Engineering, 2016)
A study on the effect of glass fibers/rubber composites on the grip on ice has been conducted in order to develop new materials for ski boot soles with increased grip in winter environments. The study has been conducted analyzing the friction of a composite material and of a ski boot sole containing an insert made of the composite material and comparing the results with those obtained using rubber and a thermoplastic elastomer. The analysis of the morphology of the composite surface, by Scanning Electron Microscopy, shows a homogenous distribution of glass fibers of approximately 10 ?m of diameter in the rubber matrix. Moreover, the measure of the contact angle shows that the composite material has a higher water repellency compared to the rubber matrix. The measure of the coefficient of friction indicates a significant effect of the glass fibers on the grip on icy surfaces. The increased grip can be ascribed to the stiffness of the glass fibers that are able to have a mechanical grip on the ice surface and to the increased contact angle and water repellency of the composite that decrease the formation of a water layer below the sole.